ŹRÓDŁA EKSPANSJI CYWILIZACJI EUROPEJSKIEJ - Daszkiewicz, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article addresses the problems of the sources of the expansion of European civilization. They are essential to understand why it were the Europeans who managed to impose their civilization on the whole world, although other cultural circles, such as the Empire of the Steppes, China or the Islamic world, were equally able to do so. The answer involves a set of factors specific to Europe and non-existent in the same configuration elsewhere; the factors include geographic diversity, political pluralism and free trade, military revolution, transoceanic shipping and accumulation of capital, science, technology and printing, ship and rational explorer.